Reaction of Electrogenerated Ligand-Reduced Nickel Salen with Benzyl Bromide, 1-Bromomethylnaphthalene, and α-Bromodiphenylmethane: A Study of Steric Effects. Issue 2 (1st January 2016) - Nguyen, Minh-Anh N.; Tomasso, Maria E.; Easter, David C.; Ji, Chang
Abstract : Cyclic voltammetry (CV) and controlled-potential electrolysis (CPE) were employed to examine the reactions of electrogenerated ligand-reduced nickel(II) salen with benzyl bromide, 1-bromomethylnaphthalene, and α-bromodiphenylmethane. Cyclic voltammograms for nickel(II) salen in the presence of benzyl bromide or 1-bromomethylnaphthalene exhibit characteristic features for the catalytic reduction of substrates involving radical intermediates. Bulk electrolyses of benzyl bromide and 1-bromomethylnaphthalene at carbon cathodes catalyzed by nickel(II) salen were also carried out at selected potentials to afford various products. These results were compared with similar reaction involving 1-bromooctane as the substrate. Further comparison of the CVs for nickel(II) salen before and after reactions with the four different organic halides reveals that the steric effect could play an important role in the corresponding nucleophilic attack of the substrates by ligand-reduced catalyst (a radical−anion), which follows the sequence of 1-bromooctane > benzyl bromide > 1-bromomethylnaphthalene > α-bromodiphenylmethane in terms of reaction efficiency. Moreover, theoretical calculations using density functional theory were carried out to establish a proposed mechanism for the electrochemical reactions on the basis of previous and current studies.